Permeability change and geometrical information of void spaces in Berea sandstone and Otway sandstone. Issue 1 (2nd January 2017) - Cheon, Dae-Sung; Takahashi, Manabu; Park, Eui-Seob
Abstract: To clarify the differences in permeability and three-dimensional void geometry in two sandstones, permeability change by increasing confining pressure were measured and three-dimensional geometrical information with microfocus X-ray CT were analyzed. In this research, Berea sandstone and Otway sandstone were used as a specimen, and its total porosity measured by mercury intrusion porosimetry were 17.4 and 25.0%, respectively. Pore size distribution in both sandstones was almost same as one modal manner, but Otway sandstone specimen showed slightly narrow peak of 5 μ–7 μm. Permeability change in both sandstones was decreased with increasing effective confining pressure, but the absolute value in Otway sandstone was lower by one order of magnitude than those in Berea sandstone. Three-dimensional medial axis (3MDA) method was adopted to compare pore geometry in two sandstones and tortuosity, number of connecting paths were decided. Based on this information, we evaluated the relationship between permeability and pore structures.